Determination of Russian innovative activity tendencies - Marina A. Motova (Статистика и экономика, 2016)
There is an attempt to group main types of economic activity depending on intensity and efficiency of innovative activities on the basis of the available statistical information on dynamics of innovative activities in various industries of economy and with the use of the mathematic and statistical tool, in particular, cluster analysis tool. For this purpose, on the basis of the data, contained in the statistical report, characterizing the level of innovative activity (number of the innovation-active organizations, costs for technological innovations, amount of the shipped innovative products, etc.) the indicators, characterizing intensity and efficiency of innovative activities were calculated. They have acted as the initial information for implementation of the cluster analysis.Further analysis results of the data, characterizing profitability of investments in various industries of economy are presented. Obviously, the activity of implementation of financial investments in various sectors of industrial production and service sector are directly connected with the profit on financial investments. On the basis of the dynamics analysis of investments’ profitability in various industries of economy for the period of 2005-2014 leaders and outsiders in this indicator are revealed. The following conclusion is made: the need to develop the forecast estimations on the indicators, characterizing profitability of financial investments on main types of economic activity.The analysis of innovative activities in the Russian Federation (results are given in the article), is based on the official statistics data. The main source of statistical information is the report «Information about innovative activity of organization «. The data, obtained as a result of the observation, are published in the editions «Indicators of Innovative Activity» (The Ministry of Education and Science of the Russian Federation, Federal State Statistics Service (Rosstat) and Higher School of Economics) and «The Russian Statistical Year-Book» of Rosstat.Data on a condition of the innovative sphere in Russia, and, also data on profitability of financial investments cover the industrial production (the extracting and processing productions and the enterprises on production and electric power, gas and water distribution), and also some industries of the service sector. The analysis covers the data for the period of 2005-2014. It covers the data on the innovation-active organizations, engaged in technological innovations by main types of economic and innovative activity. In total the given results, from our point of view, can become a basis for the choice of the directions of investment activity.Development of forecasts of the main indicators of the innovative sphere shall become the perspective direction of research continuation. The received forecasts will be the basis for the cluster analysis procedure for the purpose of prospects’ determination for the development of investment activity in innovation-active sectors of economy